Diffusion Characteristics of Particles on Energetically Disordered Lattices - Mung, Trinh Van; Hung, Pham Khac; Nguyen, Pham Ngoc (Communications in Physics, 2011)
We present here the result of MC simulation for diffusion of particles in the lattices with both types of disorders. We have calculated the correlation factor F, the mean time between two subsequent jumps and the coverage dependence of diffusion coefficient. It is shown that the character of particle migration depends on the type of energetic disorder. The lattice inhomogeneity produces specific peculiarities on the coverage dependence of diffusion coefficient. For the lattice of site disorder and two-level distribution we observe an anomalous behavior of diffusion at low concentration of low energy level and at low temperature